Comparative measurement properties of constant work rate cycling and the endurance shuttle walking test in COPD: the TORRACTO® clinical trial. (May 2020) - Maltais, François; O'Donnell, Denis E.; Hamilton, Alan; Zhao, Yihua; Casaburi, Richard
Background: Exercise tolerance is an important endpoint in chronic obstructive pulmonary disease (COPD) clinical trials. Little is known about the comparative measurement properties of constant work rate cycle ergometry (CWRCE) and the endurance shuttle walking test (ESWT). The objective of this sub-analysis of the TORRACTO ® study was to directly compare the endurance measurement properties of CWRCE and ESWT in patients with COPD in a multicentre, multinational setting. We predicted that both tests would be similarly reliable, but that the ESWT would be more responsive to bronchodilation than CWRCE. Methods: This analysis included 151 patients who performed CWRCE and ESWT at baseline and week 6 after receiving once-daily placebo, tiotropium/olodaterol (T/O) 2.5/5 μg or T/O 5/5 μg. Reproducibility was assessed by comparing their respective performance at baseline and week 6 in the placebo group. Responsiveness to bronchodilation was assessed by comparing endurance time at week 6 with T/O with baseline values and placebo. The locus of symptom limitation and end-exercise Borg scales for breathing and leg discomfort for both tests were also analysed. Results: The intraclass correlation coefficients for CWRCE and ESWT were 0.56 [95% confidence interval (CI) 0.37–0.71] and 0.75 (95% CI 0.63–0.84). More patients were limited by breathing discomfort during the ESWT than during CWRCE, whereas more patients were limited by leg discomfort or breathing/leg discomfort during CWRCE than the ESWT ( p  <0.0001). Both tests were responsive to bronchodilator treatment: there was a 19% increase in endurance time from baseline at week 6 ( p  = 0.0006) assessed with CWRCE, and a 20% increase in endurance time assessed with ESWT ( p  = 0.0013). Conclusions: Both exercise tests performed well in a multicentre clinical trial. Although the locus of symptom limitation differed between the two tests, both were reliable and responsive to bronchodilation. For future clinical trials, the choice of test should depend on the study requirements. ClinicalTrials.gov identifier: NCT01525615. The reviews of this paper are available via the supplemental material section.